2021
DOI: 10.3390/agronomy11010100
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth, Yields and Fruit Quality of Processing Tomato (Solanum lycopersicon L.) as Affected by the Combination of Biodegradable Mulching and Digestate

Abstract: In order to improve environmental sustainability of tomato cultivation and the quality of the harvested fruits, we tested (a) the digestate from anaerobic fermentation of buffalo slurries as partial replacing of NP fertilizers and (b) the biodegradable mulching to improve the nutrients and water availability for crop and to control weeds. In 2017–2018, a private farm of Campania region hosted a trial with four treatments deriving from the combination of two experimental factors: (1) fertilization strategy (sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
7
6
1
Order By: Relevance
“…As regards the total soluble solids of tomato fruits, mulching elicited almost a 10% increase compared to bare soil; our data are consistent with those of Morra and colleagues [28] who recorded a significant increase in TSS of fruits of plants grown on biodegradable mulching film compared to bare soil (about +5.0% and 9.0% in two experimental years). Contrarily, Mendoca et al [21], who compared six different colored plastic mulching films, a rice straw biodegradable film, and soil not covered, did not record a difference in TSS.…”
Section: Discussionsupporting
confidence: 92%
“…As regards the total soluble solids of tomato fruits, mulching elicited almost a 10% increase compared to bare soil; our data are consistent with those of Morra and colleagues [28] who recorded a significant increase in TSS of fruits of plants grown on biodegradable mulching film compared to bare soil (about +5.0% and 9.0% in two experimental years). Contrarily, Mendoca et al [21], who compared six different colored plastic mulching films, a rice straw biodegradable film, and soil not covered, did not record a difference in TSS.…”
Section: Discussionsupporting
confidence: 92%
“…Liquid and solid digestate fractions led to crop performances (e.g., dry biomass, plant height, LAI) that were consistently comparable to those of mineral fertilizers. On the one hand, this confirms the good potentialities of by-products as digestate for N delivering and maintaining crop performances [2,20,21,[36][37][38]. On the other hand, this may suggest that the adoption of different N rates is more suitable compared with adopting an equal rate when different fertilizers (e.g., organic and mineral) are involved, in order to homogenize crop performances and evaluate the cropping system agro-environmental sustainability in a holistic way.…”
Section: Discussionsupporting
confidence: 52%
“…At day zero, the OTRef (53.55 N) showed the highest value of firmness compared to other samples; however, the decrement was seen gradually over the period of storage at both ambient and refrigerated conditions. Additionally, loss of firmness was observed more in the case of Morra et al [22] reported implementation of organic soil amendments such as buffalo slurry resulted in increased firmness of the tomato fruit.…”
Section: Physical Parametersmentioning
confidence: 99%